Application of breather solutions for the investigation of wave/structure interaction in high steep waves - Clauss, Günther F.; Klein, Marco; Dudek, Matthias; Onorato, Miguel (Volume 2: Structures, Safety and Reliability, 2012)
During the design process of floating structures, different specifications have to be aligned such as the range of application, the warranty of economical efficiency as well as the reliability and are an inevitable integral part of the evaluation process during the design stage. The validation of the performance by means of model tests in terms of sea state behavior and the associated local and global structural loads are an important milestone within this process. Therefore it is necessary to determine an adequate test procedure which covers all essential areas of interest. Thereby one field of interest are limiting criteria of the design such as maximum local and global loads as well as maximum accelerations due to the impact of extraordinarily high waves, at which the floating structure has to survive. Different alternatives are available to conduct model tests in high, steep waves - transient wave packages, regular waves, irregular waves with random phases or more sophisticated deterministic tailored irregular wave sequences such as reproductions from numerical simulations and real-world measurements. This paper introduces a new approach for the systematic investigation of wave/structure interaction in high, steep waves. Exact solutions of the nonlinear Schrödinger equation - the so called breather solutions - are implemented for the generation of extraordinarily high waves. Three types of breather solutions are investigated in the seakeeping basin and to cover the full range of interest, each solution has been used to generate freak waves at certain frequencies. To evaluate the applicability of breather solutions for model tests two types of ships - a LNG Carrier and a Chemical Tanker - are investigated in the seakeeping basin. The ships are segmented and connected with strain gauges to detect the vertical wave bending moment. Furthermore, green water probes are installed on deck to evaluate the local impact on the bow of the freak waves. The obtained results are compared to investigations in regular waves ...